2015
DOI: 10.1099/jmm.0.000153
|View full text |Cite
|
Sign up to set email alerts
|

Frequent topoisomerase IV mutations associated with fluoroquinolone resistance in Ureaplasma species

Abstract: This study aimed to investigate the role of quinolone resistance-determining regions (QRDRs) of DNA gyrase (encoded by gyrA and gyrB) and topoisomerase IV (encoded by parC and parE) associated with fluoroquinolone resistance. A total of 114 Ureaplasma spp. strains, isolated from clinical female patients with symptomatic infection, were tested for species distribution and susceptibility to four fluoroquinolones. Moreover, we analysed the QRDRs and compared these with 14 ATCC reference strains of Ureaplasma spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
6
16
1
Order By: Relevance
“…A 2015 study performed in China uncovered the first phenotypic evidence of LVX r associated with an S83W NSS in a U. parvum isolate. Their corresponding MICs (levofloxacin, 4 g/ml; ciprofloxacin, 16 g/ml) matched those of our levofloxacin-resistant isolate (26). Recent studies in the United States, Japan, and England and a review cataloguing mutations in Ureaplasma species isolates from 2006 to 2016 found that the S83L substitution in parC solely accounted for LVX r in the majority of isolates (range, 55 to 87%) examined (17,19,24,25,27).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A 2015 study performed in China uncovered the first phenotypic evidence of LVX r associated with an S83W NSS in a U. parvum isolate. Their corresponding MICs (levofloxacin, 4 g/ml; ciprofloxacin, 16 g/ml) matched those of our levofloxacin-resistant isolate (26). Recent studies in the United States, Japan, and England and a review cataloguing mutations in Ureaplasma species isolates from 2006 to 2016 found that the S83L substitution in parC solely accounted for LVX r in the majority of isolates (range, 55 to 87%) examined (17,19,24,25,27).…”
Section: Discussionsupporting
confidence: 69%
“…Although we detected only one levofloxacin-resistant isolate, it did have an NSS identified only twice previously in Ureaplasma species clinical isolates (25,26). The first report of this mutation surfaced in a Japanese isolate (25); unfortunately, the authors were unable to cultivate the isolate for MIC testing.…”
Section: Discussionmentioning
confidence: 58%
“…However, the newer fluoroquinolones, LVX and MXF presented a greater effectiveness against Ureaplasma spp., as described elsewhere [32]. By contrast, Song et al have reported in China a higher resistance rate to LVX (76.9%) and MXF (23.1%), compared to our findings (17.82 and 0%, respectively) [33]. In our study, all isolates were resistant to ERY and moderately sensitive to AZM, which was surprising as Ureaplasma spp.…”
Section: Discussioncontrasting
confidence: 78%
“…High rates of amino acid mutations in DNA gyrase and topoisomerase IV were found in fluoroquinolone ‐ resistant Ureaplasma spp . We isolated Ureaplasma spp.…”
Section: Antibiotic Regimen For Intra‐amniotic Infection With Ureaplamentioning
confidence: 99%